Twenty Years of Workplace Health Promotion - Woolmer, Jillian; Howat, Peter; Sauer, Kay (2005)
Curtin University has been actively advocating a healthy lifestyle in the workplace to increase productivity, creativity, health and happiness for 20 years. The Curtin Healthy Lifestyle Program was initially established based on a community development approach.University staff are assisted to reduce their level of stress by promoting a healthy lifestyle and changing the work culture to one where staff are valued. Staff are encouraged to balance work, study and family life by taking work breaks, attend healthy activities during work time, be involved with campus life, network with other staff, develop hobbies, fit physical activity into their day (even involving their families in healthy activities) and generally make time to care for their health.The program focuses on intersectoral collaboration amongst various departments, areas and individuals. Staff and students are encouraged to become involved, to form supportive groups, to increase the number of healthy opportunities available and to find solutions to health related problems on campus.This paper reviews the range of activities offered at the University as part of the program, and outlines environmental and policy changes undertaken to develop a supportive environment in the workplace and the development of a "Health Promoting University".